Design and fabrication of push button coconut palm collector - Mohamad Maliki, Sulaiman (2013)
This project is about design & development of push button coconut palm collector that can be used easier and everywhere. The objectives in this project are to create an easy method to make worker easier to collect the fruit at anytime and anywhere. Besides that, to design and fabricate an apparatus that can help in drying the shoes with simple action. This project involves the process of designing the push button coconut palm collector by considering the functionality, shape, environment fitting, and the manufacturing cost for people to use it. The selection of suitable materials in the fabricating of the push button coconut palm collector is a loaded material which has minimum weight, long life-span and can detain heavy load. Material is purpose for the fabrication of the push button coconut palm collector is stainless steel. In assembled the product and parts of the product, welding process is suitable because it will heat and melt the origin metal to joining.